Tathowwur Mafhum Al-Adab Al-‘Araby: Dirasah Lughawiyah Tarikhiyyah - Ilham Ramadhan; Haniah Haniah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Arabic literature has other characteristics of world literature. Begins with the division of Arabic literature into historians and the concept of the meaning of